Pengaruh Model Pembelajaran Time Token Dan Talking Stick Terhadap Peningkatan Minat Dan Hasil Belajar Siswa Kelas V IPS SDN 106827 Desa Durian - Chintani Sihombing; Mindo Sinaga; Alexander Samosir (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2025)
This research aims to analyze. (1) The influence of learning models on student learning outcomes. (2) The influence of social studies learning outcomes on students who have high interest and students who have low interest. (3) The interaction between the learning model and the level of interest influences student learning outcomes. This research is a quasi-experimental research (quasi-experiment). This population is class V students at SD Negeri 106827 Desa Durian. The sample in this study was selected using purposive random sampling from two classes. The experimental class was treated with the time token model, the control class was treated with the Talking Stick model. The instruments used consisted of: learning results tests and learning interest questionnaire sheets. Data analysis was carried out using two-way ANOVA. The results of this research indicate that the time token learning model is a solution and alternative for teachers to improve students' social studies learning outcomes.